Long-term outcome following laser therapy of benign cystic-solid thyroid nodules. Issue 7 (July 2019) - Døssing, Helle; Bennedbæk, Finn Noe; Hegedüs, Laszlo
Abstract : Objective: Laser therapy (LT) is considered a safe and effective procedure for inducing thyroid nodule necrosis, fibrosis and shrinkage. Little is known about long-term efficacy of LT in benign complex thyroid nodules, which we report here. Design and methods: One hundred and ten euthyroid outpatients (28 men and 82 women; median age 48 years (range 17–82)) with a recurrent cytologically benign cystic (≥2 mL cyst volume) thyroid nodule causing local discomfort were assigned to LT. LT was performed after complete cyst aspiration and under continuous ultrasound (US) guidance. Nineteen patients (17 within 6 months) had surgery after LT. The median follow-up for the remaining 91 patients was 45 months (range: 12–134). Results: The overall median nodule volume in the 110 patients decreased from 9.0 mL (range: 2.0–158.0) to 1.2 mL (range: 0.0–85.0) ( P < 0.001) at the final evaluation, corresponding to a median reduction of 85% (range: −49 to 100%). Remission of the cystic part (volume ≤1 mL) was obtained in 82 of 110 (75%) patients after LT. The median cyst volume decreased from 6.3 mL (range: 2.0–158.0) to 0.0 mL (range: 0.0–85.0) ( P < 000.1), corresponding to a median reduction of 100% (range: −49 to 100%). These results correlated with a significant decrease in pressure as well as cosmetic complaints. Side effects were restricted to mild local pain. Conclusion: US-guided aspiration and subsequent LT of benign recurrent cystic thyroid nodules results in a satisfactory long-term clinical response in the majority of patients. LT constitutes a clinically relevant alternative to surgery in such patients.